2018
DOI: 10.21926/obm.transplant.1901052
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Human Islet Processing: Manufacturing Steps to Achieve Predictable Islet Outcomes from Research Pancreases

Abstract: Background: This presentation of a six-year study processing human islets for research and transplantation includes a review of multi-center transplant studies identifying key variables critical for successful islet processing and defines standardized processing procedures required to provide highly purified, functional Human Islets. Methods: Human islet processing methods are defined in detail with pancreas retrieval, shipping, trimming for processing, collagenase distension, controlled digestion by digestion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Adult human pancreatic islets from seven brain-dead donors were generated by Prodo Laboratories (Aliso Viejo, CA) according to the standard procedures [ 25 ]. Islets were harvested from pancreata from deceased organ donors without any identifying information and with informed consent properly and legally secured, and Western Institutional Review Board (WIRB) approval.…”
Section: Methodsmentioning
confidence: 99%
“…Adult human pancreatic islets from seven brain-dead donors were generated by Prodo Laboratories (Aliso Viejo, CA) according to the standard procedures [ 25 ]. Islets were harvested from pancreata from deceased organ donors without any identifying information and with informed consent properly and legally secured, and Western Institutional Review Board (WIRB) approval.…”
Section: Methodsmentioning
confidence: 99%
“…The complexity of pancreas transplant viability reminds scientists and clinicists that there are other perspectives and alternatives to PTx -bioengineering and islets auto transplantation, when it is possible [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Although islet isolation protocols have advanced considerably over the last 30 years, there are several areas of opportunity to improve islet quality and quantity. In this special issue, a comprehensive multicenter and multi-year report by Scharp et al [1] summarizes several factors that have been shown to be consistently associated with improved islet yield, as well as insulin responsiveness and content, including active enzyme digestion time (i.e., switch time), older age and longer ischemia time. This relevant work by Sharp et al challenges the notion that islet isolation techniques have 'reached their peak' and are unlikely to be amenable to substantial improvements.…”
Section: Advances and Remaining Challenges With Islet Isolationmentioning
confidence: 99%